2011
DOI: 10.1089/vbz.2010.0028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Dengue NS1 Ag Strip®for Detection of Dengue Virus Antigen inAedes aegypti(Diptera: Culicidae)

Abstract: Dengue fever is currently one of the most important mosquito-borne diseases that affect humans. With neither vaccines nor treatment available, prevention of the disease relies heavily on surveillance and control of mosquito vectors. In the present study, we have evaluated and showed the potential use of the Dengue NS1 Ag Strip Ò for the detection of dengue virus (DENV) in Aedes aegypti. Initial results showed that the sensitivity of the test kit in detecting DENV in wild-caught mosquitoes is comparable to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 18 publications
4
47
0
Order By: Relevance
“…23,32,33 Viral tissue tropisms and load also may be different in intrathoracically infected mosquitoes as compared with orally infected mosquitoes and could affect the efficacy of the respective tests. However, the previous study by Tan and others, 28 which used Bio-Rad's Dengue NS1 Ag Strip test, showed that detection of DENV NS1 antigen was successful for both orally infected and field collected specimens. Interestingly, in our studies DENV NS1 could be detected using the Platelia NS1 Ag kit in nearly all of the pools that tested false negative by RT-PCR/nested PCR.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…23,32,33 Viral tissue tropisms and load also may be different in intrathoracically infected mosquitoes as compared with orally infected mosquitoes and could affect the efficacy of the respective tests. However, the previous study by Tan and others, 28 which used Bio-Rad's Dengue NS1 Ag Strip test, showed that detection of DENV NS1 antigen was successful for both orally infected and field collected specimens. Interestingly, in our studies DENV NS1 could be detected using the Platelia NS1 Ag kit in nearly all of the pools that tested false negative by RT-PCR/nested PCR.…”
Section: Discussionmentioning
confidence: 90%
“…The monoclonal antibody used in the test has been shown to detect the NS1 protein of all 4 DENV serotypes, albeit with some differences in sensitivity. 37 Moreover, Tan and others 28 showed that all 4 DENV serotypes could be readily detected in infected mosquitoes using the Dengue NS1 Ag Strip test from the same manufacturer as the Platelia Dengue NS1 kit. Nonetheless, it would be prudent to determine the ability to detect DENV-1, -3, and -4 NS1 in mosquitoes subjected to the simulated field collection conditions by use of the Platelia Dengue NS1 Ag kit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of the NS1 antigen capture kit for the detection of DENV antigens from Ae. aegypti mosquitoes has recently been demonstrated (Tan et al 2011). However, none of the other techniques that were available could confirm infection or verify the infecting serotype.…”
Section: Simplexa™ Dengue Real-time Rt-pcr -mentioning
confidence: 99%